PENGARUH FAKTOR SPESIFIK BANK DAN MAKRO EKONOMI TERHADAP RISIKO KREDIT PERBANKAN DI INDONESIA - Sparta Sparta (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2015)
These research goals are to examine the effect of the bank-specific and macroeconomic variable to the level of risk in Indonesia. The sample is 107 conventional banks in Indonesia and the number of observation in 1177 during the period 2001 to 2011. Bank risk measurement uses the ratio of non-performing loans. The dependent variable used is non-performing loans. The independent variables are capital adequacy, asset growth, the percentage of foreign ownership, the percentage of government ownership, the percentage of public ownership, GDP growth and the bank loan growth. This study provides empirical evidence banks risk are positively significant influenced by the bank risk last year and negatively significant influenced by GDP growth. Other independent variables as capital adequacy, asset growth, the percentage of foreign ownership, the percentage of government ownership, the percentage of public ownership, and the bank loan growth not influenced by bank credit risk in Indonesian. Empirical results of this study have implications for practitioners banks, institutions banking authorities or the FSA and the development of the theory of risk associated with specific bank factors and macroeconomic factors that influence banking credit risk as the results of this study.